Digital Startups Fundamental Capabilities in New Product Development: Multiple Case Studies in Bandung, Indonesia - Retna Ayu Mustikarini Kencanasari; Wawan Dhewanto (Jurnal Manajemen Indonesia, 2022)
Digital startups compete by increasing their ability to innovate in new product development. New product development becomes one of the main processes for startups to scale their product quality. As there are many frameworks of new product development to follow, the particular new product development in digital startups should be established to contribute to the theory. Therefore, the research question of this study is: What are the fundamental capabilities of new product development in digital startups. This research uses the exploratory study approached by qualitative research, interviewing at least CEOs of four digital startups in Indonesia and a technology-based new ventures expert. From the study, there are three influential capabilities in the new product development in digital startups, such as financial, market, and technology. The connection between capabilities contributes to the theoretical framework. The implication of this study is to help practitioners to conduct an ideal new product development process. Keywords—Digital Startups ; Financial Capability; Market Capability; New Product Development; Technology Capability.